(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Recent technological advancements are reshaping the future of the healthcare system. Recognizing the factors contributing to depression is crucial for advancing research and developing innovative therapies, given the increasing prevalence of depression as a major global public health concern